Representation of social actors in news discourse of countries affected by disasters - Md Adnan, Wan Najmiyyah Wan; Shamsudin, Sarimah (Opción, 2019)
This paper explores the process of conceptualizing the framework for the representation of social actors in news discourse of countries affected by MH370 and MH17 disasters. This study built its conceptual framework based on a series of systematic methodology. As a result, a conceptual framework is established based on the construction of self and other representations in critical discourse analysis, attitude sub-system from appraisal theory and corpus linguistics. In conclusion, this paper argues that a wholesome approach is required because previous research lack discussions on the representation of social actors in news discourse of countries affected by aviation disasters.